Pengaruh Security Privacy, Performance Expectancy, dan Social Influence Terhadap Behavioral Intention dengan Perilaku Konsumen Sebagai Variabel Moderasi Pada Pengguna Livin By’ Mandiri di Kota Bengkulu - Salsabila Zaharani; Veny Puspita; Fauzan (Program Studi Manajemen dan Magister Manajemen, Fakultas Ekonomika dan Bisnis, Universitas Katolik Widya Mandira, 2025)
This study aims to determine the influence of factors such as security and privacy, performance expectations, and social influences on user behavioral intentions in using the Livin' by Mandiri application in Bengkulu City. In addition, this study also examines the role of consumer behavior as a moderating variable that can strengthen or weaken the relationship between these factors and user behavioral intentions. The research method used is a quantitative approach with data collection through questionnaires. The findings show that all major factors have a positive influence on user behavioral intentions. Perceptions of security and privacy, expectations of effective application performance, and social support from the surrounding environment contribute to increasing user intentions to continue using this digital banking application. On the other hand, consumer behavior not only has a direct influence on behavioral intentions but also functions as a strengthener of the relationship between the three main factors and application usage intentions. The results of this study provide important implications for application developers and financial institutions to pay attention to aspects of security, convenience, and social support in developing digital service development strategies. In addition, building active and positive consumer behavior towards technology is also the key to the success of sustainable application adoption.